847 Successfully implementing information systems to improve occupational health and safety performance – 1: challenges and opportunities. (24th April 2018) - Spiegel, JM; Jones, D; Darwin, L; Adu, P; Yassi, A
Abstract : Introduction: Although information systems (IS) have been widely applied to address health concerns worldwide, few initiatives address workers health and safety. This is especially the case in the health sector, an area the High Level Commission on Health Employment and Economic Growth acknowledged to be in need of attention, particularly in low and middle-income countries. Methods: Applying a context-mechanism-outcome study design, we analyse how a comprehensive IS initially introduced in Canada was successfully transferred to South Africa (SA) through a partnership of two WHO Collaborating Centres in Occupational Health and Safety. We particularly explore contextual (socio-political and technological) characteristics at micro, meso and macro levels and the processes applied have affected outcomes. Results: Despite limited success in initial piloting in a resource stressed provincial health department, a technology transfer partnership relying on SA technical IS core capacities and management commitment to maintain systems enabled successful application of OHASIS (Occupational Health and Safety Information System) through South Africa's National Health Laboratory Service. Success has been observed through patterns of use (incident investigation, hazard assessment, workforce health) of the system and the development of new modules to meet additional management needs (e.g. waste management, audits). Application of OHASIS is presently being scaled up in the Gauteng province health sector and in Namibia, with considerable additional interest in wider application being expressed. Discussion: The efficacy of technical systems to enable surveillance of health and safety consequences for workers together with consideration of the workplace factors and processes that affect this is necessary but not sufficient for success. Documentation of how the system is implemented (possible through analysis of the analytics of use) as well as how analysis of evidence can enable ongoing research and management improvement is critical to ensuring that commitments are maintained and the reports needed by users are made available.